Review of Leaf Unhealthy Region Detection Using Image Processing Techniques - S. A. Dhole; Rukaiyya Pyarelal Shaikh (Institute of Advanced Engineering and Science, 2016)
Abstract- In agricultural field the plants comes to an attack from the various pets bacterial and micro-organism diseases. This diseases attacks on the plant leaves, steams, and fruit part. This present review paper discussed the image processing techniques which is used in performing the early detection of plant diseases through leaf feature inspection. the basic objective of this work is to develop image analysis and classification techniques for extraction and finally classified the diseases present on leaf. Image of leaf is captured and the process is performed and to determine the status of each plant. Here proposed model divide into four parts. The image preprocessing including normalization and contrast adjustment; segment the region of interest determine by using color transform YCbCr and bi-level thresholding for statistical usage to determine the defect and severity area of plant leaves. The texture feature extraction using statistical GLCM (Gray Level Co-occurrences Matrix) and color feature by means values.[1] Finally classification achieved using random markov model.